2016
DOI: 10.1002/jts.22075
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trajectories of PTSD in Vietnam‐Era Veterans: The Course and Consequences of PTSD in Twins

Abstract: We estimated the temporal course of posttraumatic stress disorder (PTSD) in Vietnam-era veterans using a national sample of male twins with a 20-year follow-up. The complete sample included those twins with a PTSD diagnostic assessment in 1992 and who completed a DSM-IV PTSD diagnostic assessment and a self-report PTSD checklist in 2012 (n = 4,138). Using PTSD diagnostic data, we classified veterans into 5 mutually exclusive groups, including those who never had PTSD, and 4 PTSD trajectory groups: (a) early re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
1
29
2
1
Order By: Relevance
“…Participants were male Vietnam‐era twins enrolled in the VETR, a national sample of male twin pairs who served in the military between 1964–1975 (Goldberg, Curran, Vitek, Henderson, & Boyko, ). Participants completed an initial mailed survey in 1987 (Tsuang et al., ), and their physical and mental health was re‐assessed via mailed survey and telephone interview in 2010–2012 (Magruder et al., ), from which these data were drawn. Twins provided written informed consent, and the study was reviewed by the appropriate institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were male Vietnam‐era twins enrolled in the VETR, a national sample of male twin pairs who served in the military between 1964–1975 (Goldberg, Curran, Vitek, Henderson, & Boyko, ). Participants completed an initial mailed survey in 1987 (Tsuang et al., ), and their physical and mental health was re‐assessed via mailed survey and telephone interview in 2010–2012 (Magruder et al., ), from which these data were drawn. Twins provided written informed consent, and the study was reviewed by the appropriate institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details are available elsewhere (Magruder et al., ). A number of studies have reported the prevalence of PTSD and other psychiatric (Goldberg et al., , 2014; Magruder et al., ) and physical health conditions (Vaccarino et al., , ) in this follow‐up sample and have demonstrated that the weighted lifetime prevalence of PTSD among veterans who served in the war theater was 17.6 and 8.9% among non‐theater veterans (Goldberg et al., ). The prevalence of other psychiatric disorders varied as a function of PTSD diagnostic status (Goldberg et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, over 58 years, 38% of primary care patients with PTSD experienced PTSD recovery, while 30% experienced PTSD recurrence (Pérez Benítez et al, 2012). Studies that span decades have described symptom trajectories for subgroups of veterans with PTSD, such as early recovery, late recovery, late onset, and chronic (Magruder et al, 2016). Long-term followup with veterans has documented that many continue to have PTSD 20 to 40 years following military service and combat exposure (Magruder et al, 2016;Marmar et al, 2015).…”
mentioning
confidence: 99%
“…Studies that span decades have described symptom trajectories for subgroups of veterans with PTSD, such as early recovery, late recovery, late onset, and chronic (Magruder et al, 2016). Long-term followup with veterans has documented that many continue to have PTSD 20 to 40 years following military service and combat exposure (Magruder et al, 2016;Marmar et al, 2015). Among veterans and nonveterans with AUD alone, short-term (e.g., 3 year) and long-term (e.g., 25 year) studies describe different trajectories of AUD (Cranford, Krentzman, Mowbray, & Robinson, 2014;Jacob, Blonigen, Koenig, Wachsmuth, & Price, 2010).…”
mentioning
confidence: 99%
“…Lifetime prevalence of PTSD among adult Americans is estimated at about 6.8% (Kessler, et al, 2005);however, some populations may have much higher risk. For example, the prevalence of PTSD may be twice as high in females as in males (Kessler et al, 2005), while lifetime prevalence among veterans may reach 15–20% (Hoge, et al, 2004; Magruder, et al, 2016), presumably reflecting stressors such as deployment, wartime service, and exposure to combat (Dohrenwend, et al, 2006; Kessler, et al, 1995; Wolfe, et al, 1999). Given the prevalence and costs of PTSD, better understanding of how avoidance is acquired and expressed could lead to the development of better therapeutic strategies to manage or reduce PTSD symptoms(PTSS) , as well as ways to identify individuals at highest risk for PTSD following trauma exposure.…”
Section: Introductionmentioning
confidence: 99%